2006
DOI: 10.3171/jns.2006.104.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamic changes gauged by transcranial Doppler ultrasonography in patients with posttraumatic brain swelling treated by surgical decompression

Abstract: Decompressive craniectomy results in a significant elevation of cerebral BFV in most patients with traumatic brain swelling and transtentorial herniation syndrome. The increase in cerebral BFV may also occur in the side opposite the decompressed hemisphere; the cerebral BFV increase is significantly greater in the operated hemisphere than contralaterally. Concomitantly, PI values decrease significantly postoperatively, mainly in the decompressed cerebral hemisphere, indicating reduction in cerebrovascular resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 59 publications
1
52
0
7
Order By: Relevance
“…All cases revealed positive culture results (Klebisiella pneumoniae-1, Acinetobacter baumanii-3, Proteus mirabilis-1). CSF cell count never went over 500 cells/mm 3 . Infection contributed neither to patient clinical worsening nor death (p>00.5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All cases revealed positive culture results (Klebisiella pneumoniae-1, Acinetobacter baumanii-3, Proteus mirabilis-1). CSF cell count never went over 500 cells/mm 3 . Infection contributed neither to patient clinical worsening nor death (p>00.5).…”
Section: Resultsmentioning
confidence: 99%
“…Pathophysiology of this condition remains poorly understood, and, as a consequence, results of its treatment are disappointing. Although it has been demonstrated that decompressive craniectomy may improve cerebral hemodynamics in patients presenting intracranial hypertension associated with severe brain swelling 3 , its clinical efficacy regarding outcome has not been established so far and complications have been related to this method 4 . Furthermore, clear-cut indications for performing such a procedure have not yet been delineated.…”
mentioning
confidence: 99%
“…Thus, the PI values are indicative of post-traumatic cerebral blood flow and cerebral ischaemia, as well as ICP and CPP. The PI is dimensionless, unitless and independent of angle of insonation (3,30). It is postulated that PI can be used for noninvasive estimation of ICP in patients with TBI, but it must be known that PI depends on several factors such as arterial pressure pulsatility, heart rate, cerebral perfusion pressure, arterial carbon dioxide concentration, cerebral resistance and compliance of the big vessels (7,12,30).…”
Section: Gura M Et Al: Correlation Of Pulsatility Index With Intracrmentioning
confidence: 99%
“…These ion transporters and exchangers include Na-K-Cl cotransporter-1, which plays an important role in cell swelling/brain edema. The activation of Na-K-Cl cotransporter-1 is important in astrocyte swelling by ammonia where this activation is mediated by Na-K-Cl cotransporter-1 as well as its oxidation/nitration and phosphorylation 28 . Alterations in blood-brain barrier permeability, if present, appear to play a more secondary and/or facilitating role as opposed to being the central determinant of brain water accumulation in FHF 29 .…”
Section: Role Of the Blood-brain Barriermentioning
confidence: 99%